2017
DOI: 10.1128/msphere.00215-17
|View full text |Cite|
|
Sign up to set email alerts
|

The Microtubule-Stabilizing Protein CLASP1 Associates with the Theileria annulata Schizont Surface via Its Kinetochore-Binding Domain

Abstract: T. annulata, the only eukaryote known to be capable of transforming another eukaryote, is a widespread parasite of veterinary importance that puts 250 million cattle at risk worldwide and limits livestock development for some of the poorest people in the world. Crucial to the pathology of Theileria is its ability to interact with host microtubules and the mitotic spindle of the infected cell. This study builds on our previous work in investigating the host and parasite molecules involved in mediating this inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(53 citation statements)
references
References 45 publications
2
51
0
Order By: Relevance
“…Among the proteins found were several MAPs, including CLASP1 itself, CLASP2, CAP‐Gly domain‐containing linker protein 1 (CLIP‐170), and Janus kinase and MT‐interacting protein 1 (Jakmip1). The presence of endogenous CLASP1 and CLASP2 validated our approach, as we have already shown that both proteins associate with the schizont surface (Huber et al, ). Jakmip1 interacts with both MTs and members of the Jak family (Jak1 and Tyk2; Steindler et al, ).…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…Among the proteins found were several MAPs, including CLASP1 itself, CLASP2, CAP‐Gly domain‐containing linker protein 1 (CLIP‐170), and Janus kinase and MT‐interacting protein 1 (Jakmip1). The presence of endogenous CLASP1 and CLASP2 validated our approach, as we have already shown that both proteins associate with the schizont surface (Huber et al, ). Jakmip1 interacts with both MTs and members of the Jak family (Jak1 and Tyk2; Steindler et al, ).…”
Section: Resultssupporting
confidence: 71%
“…TA03615 encodes a hypothetical protein, which is predicted to be secreted and also contains an SxIP‐motif and one FAINT (“frequently associated in Theileria ”) domain. We recently confirmed that, like Ta‐p104, TA03615 is expressed on the schizont surface and that both TA03615 and Ta‐p104 interact (directly or indirectly) with CLASP1 (Huber et al, ).…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations